2020
DOI: 10.1111/jhn.12808
|View full text |Cite
|
Sign up to set email alerts
|

A self‐determination theory analysis of reflective debrief themes about dietetic student placement experiences in hospital: implications for education

Abstract: Background Healthcare placements in dietetics education contribute significantly to student learning. Exploring students’ self‐conceptualisation of placement experiences may provide insights to better support learning. Self‐determination theory (SDT) has been used to seek insight into clinical and educational settings but has not yet been applied to dietetic placement learning. The present study investigated dietetics students’ reflections of key influences on placement learning experiences and their alignment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Progressing from extrinsic to intrinsic motivation, coupled with feelings of competence, relatedness, and autonomy in one’s professional role, strongly supports student PIF [ 21 , 22 ]. Thus, it is advantageous to view health professional student learning opportunities through the lens of SDT to optimize the professional development value of the experiences [ 19 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Progressing from extrinsic to intrinsic motivation, coupled with feelings of competence, relatedness, and autonomy in one’s professional role, strongly supports student PIF [ 21 , 22 ]. Thus, it is advantageous to view health professional student learning opportunities through the lens of SDT to optimize the professional development value of the experiences [ 19 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…To assess the HWP impact on student professional development, the 12 remaining initial codes were framed as subthemes using the main SDT themes of competence, relatedness, and autonomy. Using a method from the literature used to assess the learning impact in dietetic students [ 23 ], any codes analogous to a tenet of SDT were modified toward that construct. For example, the initial theme of “student increased confidence” was modified to “perceived competence”, and the initial theme of “increased opportunity to build patient relationships” was modified to “increased opportunity to connect with patients”.…”
Section: Methodsmentioning
confidence: 99%
“…Gupta Kriti [ 34 ] used SDT as the framework to investigate the factors underlying the adoption of massive open online courses (MOOCs). Markwell, et al [ 35 ] pointed out that constructs related to the SDT concept impact student placement, learning, and experiences. Zheng, et al [ 36 ] showed that students’ basic psychological needs for autonomy, competence, and relatedness motivated them to engage actively in learning and to have better performance and academic achievements.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…By the end of the practicum, students are required to demonstrate competence for independent practice as measured against national competency standards (Dietitians Association of Australia, 2015Australia, , 2017. The practicum is an immersive experience that provides students with an opportunity to integrate theory and practice and develop the skills and attributes of a healthcare professional (Markwell et al, 2021). Students' success on their practicum is influenced by the quality of their teaching and assessment, adequate preparation for practice (Ottrey et al, 2021), and their own personal attributes (Maher et al, 2015).…”
Section: Introductionmentioning
confidence: 99%